2012
DOI: 10.1007/s12026-012-8283-9
|View full text |Cite
|
Sign up to set email alerts
|

IL-33/ST2 axis in inflammation and immunopathology

Abstract: Interleukin-33 (IL-33), a member of the IL-1 family of cytokines, binds to its plasma membrane receptor, heterodimeric complex consisted of membrane-bound ST2L and IL-1R accessory protein, inducing NFkB and MAPK activation. IL-33 exists as a nuclear precursor and may act as an alarmin, when it is released after cell damage or as negative regulator of NFκB gene transcription, when acts in an intracrine manner. ST2L is expressed on several immune cells: Th2 lymphocytes, NK, NKT and mast cells and on cells of mye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
205
0
6

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 226 publications
(222 citation statements)
references
References 96 publications
4
205
0
6
Order By: Relevance
“…It has been revealed that IL-33 can stimulate angiogenesis and cell growth via its receptor ST2 expressed in the effecting cells (20,46). In this study we have observed that ST2 was expressed in both the adenomatous/cancerous epithelium and microvessels, whether IL- LGD: Lower grade dysplasia.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…It has been revealed that IL-33 can stimulate angiogenesis and cell growth via its receptor ST2 expressed in the effecting cells (20,46). In this study we have observed that ST2 was expressed in both the adenomatous/cancerous epithelium and microvessels, whether IL- LGD: Lower grade dysplasia.…”
Section: Discussionmentioning
confidence: 64%
“…The role of IL-33/ST2 in tumors has been investigated; however, the involvement of IL-33 in different human tumors is controversial. It has been reported that the IL-33/ST2 pathway may play an active role in inhibiting antitumor immunity, promoting metastasis in breast cancer (19)(20)(21) and acting as a crucial mediator in inflammation-associated pancreatic carcinogenesis (22).…”
Section: Introductionmentioning
confidence: 99%
“…It has been proposed that the IL-33/IL-13 axis promotes liver fibrosis (25). A number of different cell types have been identified as candidates for IL-13 production upon IL-33 stimulation, including T cells and macrophages (24,48,49 Figure 5C). …”
Section: Discussionmentioning
confidence: 99%
“…IL-33 is an IL-1 family cytokine that regulates a wide array of pathological states associated with cardiovascular disease, rheumatoid arthritis, anaphylaxis, ulcerative colitis, and pathogen infestation (9,10). Like other IL-1 family members, IL-33 can be cleaved by caspase-1, although it appears that this cleavage leads to functional inactivation (11), leading to speculation that IL-33 primarily functions as a chromatin-associated nuclear factor (12).…”
mentioning
confidence: 99%